Diet quality, psychological factors and their associations with risk factors of cardiovascular disease: a cross-sectional pilot study - Anneli Peolsson; Sanna Nybacka; Mireille Ryden; Per Leanderson (BMJ Nutrition, Prevention & Health)
Background Several modifiable risk factors, including dietary habits, are linked to cardiovascular disease (CVD) progression. However, lifestyle changes remain notoriously challenging, perhaps due to psychosocial factors. This pilot study aims to investigate the relationship between adherence to a healthy diet, CVD risk factors, psychological factors and sociodemographic variables among middle-aged adults in Sweden.Methods Data were collected from March to December 2012 in the SCAPIS diet sub-study, where a total of 200 participants aged 50–64 years were enrolled. Dietary intake was assessed using the MiniMeal-Q food frequency questionnaire, and adherence to healthy eating patterns was evaluated using the Diet Quality Index-Swedish Nutrition Recommendations (DQI-SNR). Psychological factors, stress and sleep patterns were assessed through a comprehensive questionnaire. Statistical analyses included t-tests, analysis of variance, X2 tests and logistic regression to identify predictors of unfavourable apolipoprotein (Apo) B/Apo A1 ratios.Results Out of 200 participants, 182 had complete and reliable dietary data. The majority exhibited intermediate adherence to a healthy diet, with women showing better adherence to dietary fibre intake compared with men. Women with high dietary quality had better cardiovascular profiles, including higher levels of Apo A1 and high-density lipoprotein cholesterol, lower Apo B/Apo A1 ratios and higher plasma carotenoids. Significant predictors of unfavourable Apo B/Apo A1 ratios included low socioeconomic status (SES), higher body mass index, larger waist circumference and smoking. Stratified adjusted analyses revealed distinct predictors based on SES, with depression increasing the OR of an unfavourable lipid profile by 6.41 times (p=0.019) in low SES areas.Conclusions This study highlights the potential of tailored recommendations considering socioeconomic and psychological factors. Addressing mental health and promoting physical activity may be crucial for CVD risk reduction, particularly in low SES areas. Further research is needed to confirm these findings in larger cohorts and to develop targeted interventions for diverse population groups.